RESEARCHING ANTIANGINAL PROPERTIES OF THE SS-68 COMPOUND AND FOUNDING OUT THE ROLE OF ATP-SENSITIVE K+-DUCTS IN ITS REALIZATION ON ISOLATED HEART - S. K. Bogus; A. V. Zelenskaya; K. F. Suzdalev; P. A. Galenko-Yaroshevsky (Кубанский научный медицинский вестник, 2016)
It was presented that the indole SS-68 derivative (10-6 and 10-5 М) revealed the manifested antianginal action as well as the antiarrhythmic one in experiments on rats' isolated heart, at the same time it had no considerable influence on the contractile myocardium function by the normal perfusion level. The loss of coronary vascular resistance under the influence of SS-68 was considerably restrained by glibenclamid, the blocker of ATP-sensitive K+-ducts (IKATP). The received data allowed us supposing the presence of IKATP incitant properties in SS-68.